Ischemia-related changes in circulating stem and progenitor cells and associated clinical characteristics in peripheral artery disease. (December 2015) - Saber, Rana; Liu, Kiang; Ferrucci, Luigi; Criqui, Michael H; Zhao, Lihui; Tian, Lu; Guralnik, Jack M; Liao, Yihua; Domanchuk, Kathryn; Kibbe, Melina R; Green, David; Perlman, Harris; et al.
The extent and clinical significance of stem and progenitor cell (SPC) increases in response to lower-extremity ischemia in people with peripheral artery disease (PAD) are unclear. We compared changes in SPC levels immediately following a treadmill exercise test between individuals with and without PAD. Among participants with PAD, we determined whether more severe PAD was associated with greater increases in SPCs following treadmill exercise-induced lower-extremity ischemia. We measured SPC levels in 25 participants with PAD and 20 without PAD before and immediately after a treadmill exercise test. Participants with PAD, compared to participants without PAD, had greater increases in CD34 + CD45 dim (+0.08±0.03 vs −0.06±0.04, p =0.008), CD34 + CD45 dim CD133 + (+0.08±0.05 vs −0.08±0.04, p =0.014), CD34 + CD45 dim CD31 + (+0.10±0.03 vs −0.07±0.04, p =0.002), and CD34 + CD45 dim ALDH + SPCs (+0.18±0.07 vs −0.05±0.08, p =0.054) measured as a percentage of all white blood cells. Among participants with PAD, those with any increases in the percent of SPCs immediately after the treadmill exercise test compared to those with no change or a decrease in SPCs had lower baseline ankle–brachial index values (0.65±0.17 vs 0.90±0.19, p =0.004) and shorter treadmill times to onset of ischemic leg symptoms (2.17±1.54 vs 5.25±3.72 minutes, p =0.012). In conclusion, treadmill exercise-induced lower-extremity ischemia is associated with acute increases in circulating SPCs among people with PAD. More severe PAD is associated with a higher prevalence of SPC increases in response to lower-extremity ischemia. Further prospective study is needed to establish the prognostic significance of ischemia-related increases in SPCs among patients with PAD.